Perancangan Tempat Wudhu Ergonomis untuk Meningkatkan Fasilitas Keagamaan di SD Negeri 03 Batung - Krisna Heri Wibowo; Muhammad Sagaf; Rieska Ernawati; Eli Mas’idah; Sukarno Budi Utomo (ABDI KARYA : Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the quality of religious facilities at SD Negeri 03 Batung by designing an ergonomic ablution area. The existing facilities were inadequate, hindering students' comfort and efficiency in performing ablution. The methods used included field surveys, anthropometric measurements, and infrastructure development focused on ergonomic principles. The measurements showed that the optimal height for installing faucets is 79.25 cm, with a distance between faucets of 80 cm and a distance from the faucet to the body of 39.83 cm. After implementing the new design, 85% of students reported feeling more comfortable during ablution, and queue times were reduced by 50%. In addition to improving comfort and efficiency, the facility is also safer, equipped with good drainage and textured flooring to prevent slipping. This initiative is expected to serve as a model for other schools in developing ergonomic and sustainable worship facilities, to improve the quality of students' worship experiences.